Contextual-Based Learning Videos for Sixth-Grade Elementary School Indonesian Language Content - Yana, Ni Luh Ely; Sudarma, I Komang (Universitas Pendidikan Ganesha, 2023)
Students still need to learn independently; this is due to the unavailability of interactive learning media. This research aimed at creating contextual-based learning videos for grade VI elementary school Indonesian language content. This type of research was developed using the ADDIE model. The research subjects included content, design and learning media experts, and individual and small group tests. Data collection methods in this development research used questionnaire methods and test methods. Data analysis methods and techniques were quantitative descriptive analysis techniques and t-test inferential statistics. Based on the evaluation results from content experts, the percentage was 96.66% of design expert, 92.85% of media expert, 92% of individual trial, and 99.33% of Small Group Trials. The effectiveness of developing contextual-based learning videos obtained an average posttest result of 90.54, which was in a very good qualification, more significant than the average pretest result of 46.90, which was in the poor stuff. Based on the t-test results, it was obtained that the tcount was equal to 26.448, and the t table was similar to 2.018 for db equals 42 from a significance level of 5%. The results showed that there were significant results between before and after the use of contextual-based learning videos. The research concluded that learning videos effectively improves student learning outcomes in Indonesian language content for class VI elementary school.